2015
DOI: 10.1016/j.taap.2015.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid-induced necrosis in primary human hepatocytes and in patients with obstructive cholestasis

Abstract: Accumulation of bile acids is a major mediator of cholestatic liver injury. Recent studies indicate bile acid composition between humans and rodents is dramatically different, as humans have a higher percent of glycine conjugated bile acids and increased chenodeoxycholate content, which increases the hydrophobicity index of bile acids. This increase may lead to direct toxicity that kills hepatocytes, and promotes inflammation. To address this issue, this study assessed how pathophysiological concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
201
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(214 citation statements)
references
References 49 publications
12
201
0
1
Order By: Relevance
“…However, the role of increased hepatic bile acids in the progress of ANITinduced liver injury is not known. A bile acid mixture significantly increased the mRNA expression of pro-inflammatory cytokines in vitro in our study, which is consistent with results from a previous report [5] . TCA exhibited the highest increase after ANIT treatment in our study, and this factor increases the expression of MIP-2 in rodents and IL-8 in humans [6,7] .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, the role of increased hepatic bile acids in the progress of ANITinduced liver injury is not known. A bile acid mixture significantly increased the mRNA expression of pro-inflammatory cytokines in vitro in our study, which is consistent with results from a previous report [5] . TCA exhibited the highest increase after ANIT treatment in our study, and this factor increases the expression of MIP-2 in rodents and IL-8 in humans [6,7] .…”
Section: Discussionsupporting
confidence: 94%
“…Numerous studies have suggested that the intrahepatic accumulation of bile acids may directly or indirectly cause further damage to the liver [3] . One of the hypotheses regarding the pathophysiology of cholestasis is that accumulated hepatic bile acids directly induce cell apoptosis, as supported by studies on rat hepatocytes and human hepatoma lines [4,5] . Increasing attention has been paid the physiological role of bile acids acting as pro-inflammatory signals, which may trigger hepatic CXC chemokine formation during the development of cholestatic liver injury [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…Dose-dependent stimulation of liver regeneration was also observed in mice given alisol B 23-acetate, a plant triterpenoid with FXR agonistic activity [58]. Lastly, the synthetic FXR agonist Px20350 could overcome defective regeneration in aged mice [39]. In a clinical context, impaired regeneration of the (small and/or compromised) remnant liver can result in PLF.…”
Section: Pharmacological Modulation Of Liver Regeneration By Bile Salmentioning
confidence: 92%
“…Although low bile salt levels impair liver regeneration, an intrahepatic bile salt overload causes hepatotoxic effects [39]. While diet containing 0.2 % cholic acid is stimulatory, feeding of a 1.0 % cholic acid diet resulted in mortality in hepatectomized mice indicating that toxic bile salt levels had been reached [40].…”
Section: Bile Salts and Liver Regenerationmentioning
confidence: 99%
“…Other biomarkers such as miR-122 [244247], full-length cytokeratin-18 [247250], high mobility group box 1 (HMGB1) protein [247249, 251], and argininosuccinate synthetase (ASS) [252] are generally considered indicators of mainly necrotic cell death [253]. On the other hand, increased plasma levels of the caspase-cleaved form of cytokeratin-18 [247, 248, 250, 254, 255] and activated caspases detected as enzyme activity and/or the protein by western blotting [164, 247, 249, 254], are markers of apoptotic cell death. However, due to the sensitivity of the assay, cleaved cytokeratin-18 levels should always be compared to the full-length version in order to assess the relative importance of apoptosis [247, 248, 254].…”
Section: Mitochondrial Biomarkers In Drug-induced Liver Injurymentioning
confidence: 99%